2019
DOI: 10.1016/j.ssmph.2019.100421
|View full text |Cite
|
Sign up to set email alerts
|

Do traditional economic theories of free riding behavior explain spatial clustering of HPV vaccine uptake?

Abstract: Rationale Geographic clusters of low vaccination uptake reduce the population-level efficacy of vaccination programs. However, little is known about the mechanisms that drive geographic patterns in vaccination rates. Traditional economic theory considers vaccination as a classic public good and suggests that free riding— individuals taking advantage of public goods by relying on others’ immunization behavior without contributing toward them — i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…These findings are robust to various scenarios and vignettes tested in our experiment. Our results are consistent with those by Betsch et al [ 38 ] and McKillop et al [ 29 ] showing that emphasizing the high levels of neighborhood vaccination and the social benefits of vaccination did not induce free riding behavior. Other work has shown that peer influence can inform vaccination decisions, with these effects increasing as overall vaccination rates increase [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are robust to various scenarios and vignettes tested in our experiment. Our results are consistent with those by Betsch et al [ 38 ] and McKillop et al [ 29 ] showing that emphasizing the high levels of neighborhood vaccination and the social benefits of vaccination did not induce free riding behavior. Other work has shown that peer influence can inform vaccination decisions, with these effects increasing as overall vaccination rates increase [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…More generally, social norms have been shown to affect health behaviors across a variety of contexts [e.g. 29 – 34 , see also 35 ]. Focusing on social distancing to reduce the spread of COVID-19, Wu and Huber [ 33 ] analyze survey data and find that individuals in the US are more likely to practice social distancing when they report individuals in their social network are also doing so after accounting for other demographics.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are robust to various scenarios and vignettes tested in our experiment. Our results are consistent with those by Betsch et al(19) and McKillop et al(22) showing that emphasizing the high levels of neighborhood vaccination and the social benefits of vaccination did not induce free riding behavior. Other work has shown that peer influence can inform vaccination decisions, with these effects increasing as overall vaccination rates increase.…”
Section: Discussionsupporting
confidence: 93%
“…Although vaccine externalities are ubiquitous, the evidence for a free-rider problem is not always found. McKillop et al ( 2019 ) do not uncover any evidence of free-riding in Human papillomavirus (HPV) vaccination drives in Dallas, Texas, but observe a positive and significant relationship between individual vaccine choices and average neighborhood vaccine rates. In other words, they observe clusters.…”
Section: Externalities Public Goods and The Free-rider Problem With V...mentioning
confidence: 99%